Performance Incentives within Firms: The Effect of Managerial Responsibility - Aggarwal, Rajesh K.; Samwick, Andrew A. (Journal of Finance, 2003)
ABSTRACT We show that top management incentives vary by responsibility. For oversight executives, pay‐performance incentives are $1.22 per thousand dollar increase in shareholder wealth higher than for divisional executives. For CEOs, incentives are $5.65 higher than for divisional executives. Incentives for the median top management team are substantial at $32.32. CEOs account for 42 to 58 percent of aggregate team incentives. For divisional executives, the pay– divisional performance sensitivity is positive and increasing in the precision of divisional performance and the pay– firm performance sensitivity is decreasing in the precision of divisional performance. These results support principal–agent models with multiple signals of managerial effort.